How Financial Literacy, Financial Attitudes and Personality Affect MSMe Management Behavior? Case in Bengkulu - Dwi Abdul Aziz; Intan Zoraya (Hasanuddin Economics and Business Review, 2024)
MSMEs often overlook the presence of financial management, particularly the implementation of appropriate financial management and accounting standards. As a result, financial management becomes a problem for them. Micro business actors often do not know much about accounting and their education also influences their knowledge. This research aims to determine the effect of financial literacy, financial attitudes and personality on financial management behavior among MSMEs in Bengkulu City. The population of this research is MSME entrepreneurs in Bengkulu, with taking 101 samples. To determine the samples, this study uses a random sampling technique. Finally, the research results show that financial literacy effects financial management behavior, financial attitudes and personality with 0.428. In addition, the R Square value is 0.851, meaning that Financial Literacy, Financial Attitude and Personality impact Financial Management Behavior with 85.1%. Independent variables outside the model influence the remaining dependent with 14.9%. Furthermore, MSME actors needs to improve their skills, knowledge and attitude to manage their finances sensibly. A proper financial behavior could rise with possessing an access to all the financial information that may require in order to make financial decisions.